ApoB siRNA-induced Liver Steatosis is Resistant to Clearance by the Loss of Fatty Acid Transport Protein 5 (Fatp5) - Ason, Brandon (Springer-Verlag, 2011)
The association between hypercholesterolemia and elevated serum apolipoprotein B (APOB) has generated interest in APOB as a therapeutic target for patients at risk of developing cardiovascular disease. In the clinic, mipomersen, an antisense oligonucleotide (ASO) APOB inhibitor, was associated with a trend toward increased hepatic triglycerides, and liver steatosis remains a concern. We found that siRNA-mediated knockdown of ApoB led to elevated hepatic triglycerides and liver steatosis in mice engineered to exhibit a human-like lipid profile. Many genes required for fatty acid synthesis were reduced, suggesting that the observed elevation in hepatic triglycerides is maintained by the cell through fatty acid uptake as opposed to fatty acid synthesis. Fatty acid transport protein 5 (Fatp5/Slc27a5) is required for long chain fatty acid (LCFA) uptake and bile acid reconjugation by the liver. Fatp5 knockout mice exhibited lower levels of hepatic triglycerides due to decreased fatty acid uptake, and shRNA-mediated knockdown of Fatp5 protected mice from diet-induced liver steatosis. Here, we evaluated if siRNA-mediated knockdown of Fatp5 was sufficient to alleviate ApoB knockdown-induced steatosis. We determined that, although Fatp5 siRNA treatment was sufficient to increase the proportion of unconjugated bile acids 100-fold, consistent with FATP5's role in bile acid reconjugation, Fatp5 knockdown failed to influence the degree, zonal distribution, or composition of the hepatic triglycerides that accumulated following ApoB siRNA treatment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11745-011-3596-3) contains supplementary material, which is available to authorized users.